THE SIAT YEH TRADITION IN THE TRADITIONAL VILLAGE OF JIMBARAN BADUNG REGENCY - I Wayan Sukabawa; Ni Gusti Ayu Kartika (UHN I Gusti Bagus Sugriwa Denpasar, 2025)
The Siat Yeh tradition is a cultural heritage rich in local wisdom values in the Jimbaran Traditional Village, Badung Regency. This village is unique in carrying out a traditional ceremony called Siat Yeh, a spiritual ritual that involves the community together. This ceremony was held as a form of gratitude to Sang Hyang Widhi Wasa for the blessings and abundance given to the village. Apart from the religious aspect, Siat Yeh also has an important role in maintaining the sustainability of local culture. The younger generation is actively involved in carrying out this ceremony, observing and practicing the noble values inherited from their ancestors. Through Siat Yeh, Jimbaran Traditional Village is able to maintain its cultural identity amidst the ever-growing flow of modernization. This research aims to document and analyze in more depth the meaning and role of the Siat Yeh Tradition in the lives of the people of Jimbaran Traditional Village. Through a qualitative approach, this research will reveal the cultural values, philosophy and social impacts of implementing Siat Yeh. It is hoped that the research results can make a positive contribution to our understanding of cultural diversity in Indonesia and efforts to preserve local traditions amidst globalization.